PENGARUH PENYULUHAN DENGAN METODE CERAMAH DAN POSTER TERHADAP PERILAKU KONSUMSI MAKANAN JAJANAN SISWA DI SD NEGERI NO.200402 KELURAHAN SABUNGAN JAE KECAMATAN PADANGSIDIMPUAN HUTAIMBARU KOTA PADANGSIDIMPUAN TAHUN 2016 - Dalimunthe, Enda Mora (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Behavior is actions or activities of the man himself who has a very wide expanse include: walk, talk, cry, laugh, work, study, write, read, and so on. Counseling is an effort to change human behavior conducted through educative approach. Educative approach is defined as a series of activities carried out in a systematic, planned and directed by the active participation of individuals, groups, or communities to solve the problem by taking into account the social, economic, and local culture. Sampling techniques Method in research this is stratified random sampling with a sample of 60 peoples.The research design uses one group pretest-posttest, which aims to determine the effect of counseling with a lecturing and a poster on the behavior of food. In this study an instrument or means of data collection are observation sheets, Based on the results revealed that the mean knowledge gained knowledge factor pretest posttest mean of 6.08 and 11.47 with a mean difference of 5.39. With confidence index lowest and highest -6.376 -4.404. Based on these results the value of p. obtained significancy 0.000 (p <0.05), while the attitude factor, mean attitude pretest posttest mean of 7.23 and 11.23, with a mean difference of 4.0. With confidence index lowest and highest -4.768 -3232. Based on the results obtained significancy p value of 0.000 (p <0.05), for the action factor 7:00 pretest and posttest mean attitude of 11.72, with a mean difference of 4.72. With confidence index lowest and highest -5554 3,879.Based on results obtained significancy p value of 0.000 (p <0.05) And from the above table shows that the overall result p value = 0.000 <0.05. From these results it can be concluded that Ha received or no influence Extension Methods Lecturing and Posters on behavior measures Snacks Food Consumption Students at Elementary School No. 200 402 Sub sabungan Jae 2016.